Leadership for management of high-level radioactive waste in Japan. Issue 2 (14th November 2019) - Takeuchi, Maria R H; Hasegawa, Tatsuya; Hardie, Susie M L; McKinley, Linda E; Ishihara, Keiichi N
Abstract : High-level radioactive waste (HLW) management in Japan stalled prior to selecting any candidate sites for a literature survey, the first step of a staged programme for selecting a disposal site. The situation deteriorated after the Fukushima Daiichi accident. The Nuclear Waste Management Organization of Japan has suffered a loss of national/international credibility in the geological disposal project. In this study, the authors first examine the history of HLW management in Japan, assess how leaders in different key organisations communicated with each other and identify the rationale for the resulting characteristics of the overall programme. The objective is to investigate the problems encountered and the solutions adopted from a perspective that highlights what were, in retrospect, missed opportunities. A further goal is to look to the future and, from lessons learned, to determine a leadership role to allow HLW management to move forward for the next stage of selecting candidate sites. Communication for correct scientific input between leaders of relevant organisations is of critical importance. Alliance with key organisations and commitment by the government are also required. To win credibility and sympathy with geological disposal, ethical responsibilities should be taken by leaders of these organisations. The authors assume that the quality of HLW management could be enhanced by servant leadership.